O Metodach i Wynikach Obliczeń Hiperboloidalnej Powłoki Obciążonej Parciem Wiatru - Z. Baczyński (Engineering Transactions, 1962)
This is a survey of computation methods of a hyperboloidal shell loaded by wind pressure according to the membrane theory; known in the literature, and a comparison of the computation results of a hyperboloidal shell which have been carried out by various methods. Three methods are chosen for considerations: I. The integration method of the differential equations, II. Method of finite differences, III. Method of substitute lattices. As an introduction, the theoretical foundations of these methods are discussed. The results are represented in the form of diagrams of membrane forces. Then, the differences between the values of the corresponding forces are analysed for the same shell model. It is concluded that for practical computations the methods are of the same order of accuracy and that for design purposes the method of substitute lattices is the most convenient.